Planar and SPECT ventilation/perfusion imaging and computed tomography for the diagnosis of pulmonary embolism: A systematic review and meta-analysis of the literature, and cost and dose comparison. Issue 7 (July 2015) - Phillips, J.J.; Straiton, J.; Staff, R.T.
Abstract: Diagnosing acute pulmonary embolism (PE) is an indication for scintillation V/Q imaging (planar and SPECT) and/or CTPA. This study reviews, compares and aggregates the published diagnostic performance of each modality and assesses the short-term consequences in terms of diagnostic outcomes, monetary cost, and radiation burden. We performed a formal literature review of available data and aggregated the finding using a summary receiver operating characteristic. A decision tree approach was used to estimate cost and dose per correct diagnosis. The review found 19 studies, which comprised 27 data sets (6393 examinations, from 5923 patients). The results showed that planar V/Q was significantly inferior to both V/Q SPECT and CTPA with no difference between the latter two. CTPA represents best value; £129 per correct diagnosis compared to £243 (SPECT) and £226 (planar). In terms of radiation burden V/Q SPECT was the most effective with a dose of 2.12 mSv per correct diagnosis compared with 3.46 mSv (planar) and 4.96 (CTPA) mSv. These findings show no performance difference between V/Q SPECT and CTPA; planar V/Q is inferior. CTPA is clearly the most cost effective technique. V/Q SPECT should be considered in situations where radiation dose is of concern or CTPA is inappropriate.